The Influence of Customer Satisfaction, Brand Trust and Brand Loyalty on Purchase Intention: A Study Of Mcdonald’s in Malaysia - Daisy Mui Hung Kee; Liem Gai Sin; Neo Zhan Yuan; Nelly Lau Yenn Ni; Ng Kar Wen; Ng Suk Fang; Muhammad Rayhan; Muhammad Hasyir Ali; Joseph Willy Yose; Ufairoh Aqilah Muhsyi (AIBPM Publisher, 2024)
Customer satisfaction is crucial to the success of any business. It has been studied in business and marketing since the 1970s. When customers are satisfied, brand loyalty is immediately involved. As a result, brand loyalty has received much attention in recent decades. McDonald's is the world's leading fast-service restaurant, with over 36,000 outlets worldwide and over 70 million customers served daily in more than 100 countries. Every month, McDonald's serves approximately 13.5 million customers in over 320 stores in Malaysia. The company's performance is strongly related to its high brand loyalty and customer satisfaction. This paper examines how customer satisfaction, brand trust and loyalty may influence McDonald's purchase intention in Malaysia. We applied SPSS to test hypotheses, and 150 McDonald's customers engaged in a Google form- based online survey. The findings reveal that customer satisfaction, brand trust and loyalty influence McDonald's customers purchasing intentions. Recommendations and implications were discussed.